2016
DOI: 10.17221/286/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of qualitative and quantitative properties of the wings, necks and offal of chicken broilers from organic and conventional production systems

Abstract: ABSTRACT:The aim of the present study was to investigate qualitative and quantitative properties of wings, offal (liver, heart and gizzard) and necks of chickens from organic and conventional production systems, currently available on the market for Czech consumers. Production properties (yield and weight), surface colour (lightness, redness, yellowness) and chemical indicators (dry matter, total protein, net protein, collagen, hydroxyproline, fat, ash and phosphorus) were evaluated in fresh chicken broilers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
23
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 29 publications
10
23
3
3
Order By: Relevance
“…Furthermore, Farmani and Rostammiri (2015) found that chicken skin had contained moisture of 50.78%, protein of 8.93%, fat of 38.92%, and ash of 1.28%. Our results are also in good agreement with those found by Seong et al (2015) and Abdullah and Buchtova (2016).…”
Section: Gross Chemical Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, Farmani and Rostammiri (2015) found that chicken skin had contained moisture of 50.78%, protein of 8.93%, fat of 38.92%, and ash of 1.28%. Our results are also in good agreement with those found by Seong et al (2015) and Abdullah and Buchtova (2016).…”
Section: Gross Chemical Compositionsupporting
confidence: 93%
“…For example, Abu-Salem and Abou Arab 2010found that chicken liver contained Fe of 83.65, Zn of 50.75, and of Mn 1.15 mg/g (wet weight basis). Also, Farmani and Rostammiri (2015) found that chicken skin contained phosphorous of 13.43 and Iron of 35.39 ppm.Moreover, mineral contents of liver and gizzard are in agreement with those found by Seong et al (2015) and Abdullah and Buchtova (2016).…”
Section: Minerals Contentsupporting
confidence: 89%
“…(2005b , 2008) . The higher wing yield observed in SGB could be a result of higher activity levels which promote the bone mass and supporting muscle mass accumulation, compared with CB, ( Gordon and Charles, 2002 ; Abdullah and Buchtova, 2016 ). Moreover, it has been found that layer-type males tend to have a higher percentage of leg yield and less value parts of the carcass than broilers ( Gerken et al., 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Significance (P< 0.05) was estimated by t-test and ANOVA analysis of variance, with a posthoc Tukey test to find differences between independent variances using UNISTAT 6.0 (Unistat ® Limited, London, England). All results in Figs 1-7 and Tables 1-4 of this study were used in the dissertation theses of the first author (Abdullah 2017).…”
Section: Statistical Analysesmentioning
confidence: 99%